Cattle Monitoring System: The Innovation to Increase Dairy Farmers Empowerment in Providing Animal Logistics to Anticipate Anthrax Outbreak in Boyolali Regency - Johan Bhimo Sukoco; Luluk Fauziah (Universitas Muhammadiyah Surakarta, 2022)
Boyolali Regency had a very high potential in the production of cow milk. This area dominated as much as 65% of the dairy cow population in Central Java. However, Boyolali Regency farmers found difficulties in avoiding various diseases that attack dairy cattle, such as the anthrax outbreak which became an Extraordinary Event in 2011. Therefore, the government made an innovation as a solution to anticipate the outbreak through the Cattle Monitoring System named in Indonesian as Sistem Monitoring Sapi (which later called SIMAPI as the acronym). This study aimed to describe the innovation of increasing the empowerment of dairy farmers in providing livestock logistics to anticipate an anthrax outbreak in Boyolali Regency based on information technology This study used a qualitative descriptive method. The data collection techniques used interview method, observation, and document analysis. The data validity technique used in this research was triangulation method and interactive analysis model was used as data analysis technique. SIMAPI was an innovation that has been carried out by Boyolali Regency since 2008. This system recorded each dairy cow owned by the farmer, by placing an ear tag on the ear of the cow in the form of a label labeled with a barcode made from atomic plastic. This application could accommodate 7.000 characters of information related to the identity of cows and farmers, to the health condition of the cow. Farmers or buyers can scan the ear tag barcode with the SIMAPI application to find out the health history of the cow. In the future, SIMAPI needs to be developed, considering that there were some data which need to be synchronized with other institutions, such as the Slaughterhouse or in Indonesian called Rumah Pemotongan Hewan (RPH).SIMAPI is a solution in increasing the empowerment of cattle farmers in dealing with anthrax outbreaks in Boyolali Regency. The selling value of cattle has stabilized, and buyers have given trust to cattle farmers again.